Acute leukemias - Abutalib, S. (Springer, 2008)
Better therapy of acute leukemias depends ultimately on better understanding of the distinction between leukemic and normal progenitor cells. Thus, several chapters in this volume describe current knowledge of acute leukemia biology and discuss new classification systems that have arisen consequent to emerging insights into pathogenesis. Treatment has also improved for particular types of acute leukemia. Given our intention that the book be useful to clinicians, we pay particular attention to these advances, to management of acute leukemia in general, and to development of new therapies.